ACDF plus Uncovertebrectomy versus ACDF alone for the Treatment of Cervical Spondylotic Radiculopathy: Minimum 5-Year Follow-Up - Cui, Yaqing; Zhou, Yongchun; Liu, Jun; Duan, Dapeng; Gong, Liqun; Li, Weiwei (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Objective The surgical approach for cervical spondylotic radiculopathy (CSR) is controversial. This study aims to investigate the effectiveness of the combined anterior cervical diskectomy and fusion (ACDF) and uncovertebrectomy for treatment of CSR.Methods This is a retrospective case control study. One hundred and forty-six patients with CSR who underwent two different procedures (ACDF alone [group A]) and a combination of ACDF and uncovertebrectomy [group B]) from March 2008 to April 2013 were included. The operation time, blood loss, Visual Analog Scale scores of the neck (VAS-neck) and arm (VAS-arm), Neck Disability Index (NDI) score, 36-Item Short Form Health Survey (SF-36) score, fusion segment curvature, global cervical curvature, and the rate of surgical complication were evaluated.Results There were no significant differences in the basic demographic and clinical characteristics between the two groups (p > 0.05). No significant differences were noticed in the fusion segment curvature and global cervical curvature between the two groups (p > 0.05). Whereas the operation time and blood loss in group B were greater than those in group A (p < 0.05), the VAS-neck, VAS-arm, NDI, and SF-36 scores were better in group B (p < 0.05). The surgical complication rate between the two groups was not significantly different (p > 0.05).Conclusions Clinical efficacy of ACDF plus uncovertebrectomy for the treatment of patients with CSR may be better than that of ACDF alone, but at the expense of more operation time and blood loss.
Keywords: cervical spondylosis; radiculopathy; ACDF; uncovertebrectomy